Population normative data for three cognitive screening tools for older adults in sub-Saharan Africa - William Keith Gray; Stella-Maria Paddick; Adesola Ogunniyi; Olaide Olakehinde; Catherine Dotchin; John Kissima; Sarah Urasa; Aloyce Kisoli; Jane Rogathi; Declare Mushi; Akindele Adebiyi; Irene Haule; et al. (Dementia & Neuropsychologia, 2021)
ABSTRACT In sub-Saharan Africa (SSA),cognitive screening is complicated by both cultural and educational factors, and the existing normative values may not be applicable. The Identification of Dementia in Elderly Africans (IDEA) cognitive screen is a low-literacy measure with good diagnostic accuracy for dementia. Objective: The aim of this study is to report normative values for IDEA and other simple measures [i.e., categorical verbal fluency, the Consortium to Establish a Registry for Alzheimer’s Disease (CERAD) 10-word list] in representative community-dwelling older adults in SSA. Methods: Individuals aged ≥60 years resident in 12 representative villages in Kilimanjaro, Tanzania and individuals aged ≥65 years resident within three communities in Akinyele Local Government Area, Oyo State, Nigeria underwent cognitive screening. The normative data were generated by the categories of age, sex, and education. Results: A total of 3,011 people in Tanzania (i.e., 57.3% females and 26.4% uneducated) and 1,117 in Nigeria (i.e., 60.3% females and 64.5% uneducated) were screened. Individuals with higher age, lower education, and female gender obtained lower scores. The 50th decile values for IDEA were 13 (60–64 years) vs. 8/9 (above 85 years), 10–11 uneducated vs. 13 primary educated, and 11/12 in females vs. 13 in males. The normative values for 10-word list delayed recall and categorical verbal fluency varied with education [i.e., delayed recall mean 2.8 [standard deviation (SD) 1.7] uneducated vs. 4.2 (SD 1.2) secondary educated; verbal fluency mean 9.2 (SD 4.8) uneducated vs. 12.2 (SD 4.3) secondary educated], substantially lower than published high-income country values. Conclusions: The cut-off values for commonly used cognitive screening items should be adjusted to suit local normative values, particularly where there are lower levels of education.